Two new species of Loboschiza from Cambodia and Vietnam (Lepidoptera: Tortricidae: Olethreutinae: Enarmoniini) - Heppner, John B.; Bae, Yang-Seop (Zootaxa, 2016)
Two new species of Loboschiza are described and illustrated: L. cambodiensis n. sp., from Cambodia and L. flavobasis n. sp., from Vietnam. The two new species bring the number of described species in the genus to 19.